An appetite for pests: Synanthropic insectivorous bats exploit cotton pest irruptions and consume various deleterious arthropods. Issue 6 (10th March 2020) - Cohen, Yuval; Bar‐David, Shirli; Nielsen, Martin; Bohmann, Kristine; Korine, Carmi
Abstract: Conservation biological control (CBC) seeks to minimize the deleterious effects of agricultural pests by enhancing the efficiency of natural enemies. Despite the documented potential of insectivorous bats to consume pests, many synanthropic bat species are still underappreciated as beneficial species. We investigated the diet of Kuhl's pipistrelle ( Pipistrellus kuhlii ), a common synanthropic insectivorous bat that forages in urban and agricultural areas, to determine whether it may function as a natural enemy in CBC. Faecal samples of P. kuhlii were collected throughout the cotton‐growing season from five roost sites near cotton fields located in a Mediterranean agroecosystem, Israel, and analyzed using DNA metabarcoding. Additionally, data on estimated abundance of major cotton pests were collected. We found that the diet of P. kuhlii significantly varied according to sites and dates and comprised 27 species of agricultural pests that were found in 77.2% of the samples, including pests of key economic concern. The dominant prey was the widespread cotton pest, the pink bollworm, Pectinophora gossypiella, found in 31% of the samples and in all the roosts. Pink bollworm abundance was positively correlated with its occurrence in the bat diet. Furthermore, the bats' dietary breadth narrowed, while temporal dietary overlap increased, in relation to increasing frequencies of pink bollworms in the diet. This suggests that P. kuhlii exploits pink bollworm irruptions by opportunistic feeding. We suggest that synanthropic bats provide important pest suppression services, may function as CBC agents of cotton pests and potentially contribute to suppress additional deleterious arthropods found in their diet in high frequencies.